Getto Sor . Ghetto Street - Csubrilo, Zoltán (Cinema Filmworkshop, 2009)
Verzio FF Submission Duration: 00:44:00 Lukacs is a thin old gypsy musician, who often appears in cafes, pubs or on the street. He belongs to the townscape. An inseparable part of him is his tamboura, which he takes with him wherever he goes. He is glad to play to anybody, even for no money. The authentic gypsy songs he plays raise a smile on people’s face and ensure his poor living. Lukacs’s grandson also loves music, but the music the grandson embraces is different from what his grandfather represents. The boy is interested in rap and hip-hop music. He would do anything to make this dream come true, even enrolling in a talent show. The film is trying to find out if the two genres and generations represented by Lukacs and his grandson can live together, and if the traditional Roma values have undergone any changes.